Insights into the role of nanoscale zero‐valent iron in Fenton oxidation and its application in naphthalene degradation from water and slurry systems. (3rd April 2022) - Yang, Rumin; Zeng, Guilu; Xu, Zhiqiang; Zhou, Zhengyuan; Zhou, Zhikang; Ali, Meesam; Sun, Yong; Sun, Xuecheng; Huang, Jingyao; Lyu, Shuguang
Abstract: Few researches have focused on the role of nanoscale zero‐valent iron (nZVI) in Fenton‐like process for polycyclic aromatic hydrocarbons (PAHs) removal. In this study, the naphthalene (NAP) degradation tests in ultrapure water showed that nZVI addition could enhance NAP degradation from 79.7% to 99.0% in hydrogen peroxide (H2 O2 )/Fe (II)/nZVI/NAP system at the molar ratio of 10/5/3/1, showing the excellent role of nZVI in promoting NAP removal. Multiple linear regression analysis found that the correlation coefficient between H2 O2 consumption and NAP degradation was converted from −9.17 to 0.48 with nZVI and 1‐mM H2 O2, indicating that nZVI could decompose H2 O2 more beneficially for NAP degradation. Multiple Fe (II)‐dosing and iron leaching tests revealed that nZVI could gently liberate Fe (II) and promote Fe (II)/Fe (III) redox cycle to enhance the NAP degradation. When the H2 O2 /Fe (II)/nZVI/NAP molar ratios of 10/5/3/1 and 50/25/15/1 were applied in the simulated NAP contaminated actual groundwater and soil slurry, respectively, 75.0% and 82.9% of NAP removals were achieved. Based on the major degradation intermediates detected by GC/MS, such as 1, 4‐naphthalenedione, cinnamaldehyde, and o ‐phthalaldehyde, three possible NAP degradation pathways were proposed. This study provided the applicable potential of nZVI in Fenton process for PAHs contaminated groundwater and soil remediation. Practitioner Points: nZVI enhanced the NAP degradation in Fenton‐like process. Three schemes of NAP degradation pathway were proposed. nZVI performed well in the remediation of the simulated NAP contamination. Abstract : Compared with dissolved Fe(II), nanoscale zero‐valent iron (nZVI) can activate H2 O2 more beneficially for naphthalene (NAP) degradation through liberating Fe(II) gradually and promoting Fe(III)/Fe(II) redox cycle. Therefore, nZVI performed well in Fenton‐like processes for NAP‐polluted groundwater remediation and can be applied as an alternative technology for environmental remediation. Furthermore, three possible degradation pathways of NAP in H2 O2 /Fe(II)/nZVI system have been proposed.